Conformational Analysis of Diterpene Lactone Andrographolide towards Reestablishment of Its Absolute Configuration via Theoretical and Experimental ECD and VCD Methods - Muhamad Faid A Kadir; Agustono Wibowo; Fatimah Salim; El Hassane Anouar; Khalijah Awang; Moses Kiprotich Langat; Rohaya Ahmad (Universitas Gadjah Mada, 2021)
Andrographolide, the major constituent from the terrestrial plant Andrographis paniculata is a much-studied bioactive ent-labdane diterpene lactone and has become an important medicinal intermediate. Its structure as determined by X-ray crystallography has been applied in molecular docking studies to explain biological activities. Nevertheless, recently there has been a number of conflicting reports concerning the stereochemistry at the C-14 and C-10 positions affecting the absolute configuration (AC) of the compound. Since a lack of information on the molecular flexibility of the molecule can lead to misleading conclusions on biological activity, a conformational analysis of the molecule in the solution state was necessary. The conformational analysis was performed by the Spartan14 package using the Merck Molecular Force Field (MMFF). The exciton chirality method in electronic circular dichroism spectroscopy (ECM-ECD) and vibrational circular dichroism (VCD) techniques were then jointly employed to re-establish the AC of andrographolide. Theoretical calculations were performed using TD-DFT methods by using the hybrid functionals B3LYP and CAM-B3LYP combined with 6-31G(d,p) basis set. Long-range exciton coupling of 2-naphthoyl chromophores at C-14 and C-19 led to the establishment of the AC to be 3R, 4R, 5S, 9R, 10R and 14S. Comparison between the theoretical VCD data of 14-S and 14-R stereoisomer confirmed a configuration of S at C-14 position instead of R.